2022
DOI: 10.12821/ijispm090404
|View full text |Cite
|
Sign up to set email alerts
|

Information systems project management success

Abstract: This paper aims to provide new insights into information systems (IS) project management success. Even though many studies found in the literature show results of software development projects, few studies address the success of IS (socio-technical) projects. Responses to an international survey, regarding 472 projects in total, showed that IS project management is achieving high levels of success; yet, only a minority of projects end without changes in scope, schedule or cost. Furthermore, the results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…The meditative effect of procurement practice on the relationship between e-procurement and procurement performance cannot be underestimated, as this research makes clear. A high level of information management and high-quality processes are required in addition to advanced technology for success (Varajao et al, 2021). Any delays will result in line idling, overtime payments, garment air freight, and lost sales, thus it is imperative to arrange inspection, cutting, production, and finishing as planned.…”
Section: Table 06: the Results Of The Sobel Testmentioning
confidence: 99%
“…The meditative effect of procurement practice on the relationship between e-procurement and procurement performance cannot be underestimated, as this research makes clear. A high level of information management and high-quality processes are required in addition to advanced technology for success (Varajao et al, 2021). Any delays will result in line idling, overtime payments, garment air freight, and lost sales, thus it is imperative to arrange inspection, cutting, production, and finishing as planned.…”
Section: Table 06: the Results Of The Sobel Testmentioning
confidence: 99%
“…Even though many studies found in the literature show results of software development projects, few studies address the success (socio-technical) of IST projects (Varajão et al, 2021). Considering this reality, based on the case study presented at ECTCH 2021, this study aims to analyze the success of the IST project associated with the viability of a strategic investment related to the digital transformation of the publishing warehouses' group case study.…”
Section: Methodsmentioning
confidence: 99%
“…Even when defined simply as completed technology that meets contractual requirements, the statistics are concerning. According to the Standish Group's 2020 Chaos Report on software project management (cited by Varajão et al, 2021), 31% of 2020 projects were successful (completed on time with agreed results), 50% were challenged (agreed results not met or not met within scope or schedule), and 19% were abandoned. In other cases less well documented, technology is introduced into the work system but does not integrate well.…”
Section: Introductionmentioning
confidence: 99%